Modeling of cognitive radio system for the improvement of spectrum utilization - M, Meena; M, Monish; C, Sharanya; V Rajendran, Dr (International Journal of Engineering and Technology, 2018)
Itâ€™s well inferred that the MAC layer technique on wireless network is well established and many scientists elaborately worked on this technique till the updated 5G technology. However, the present study clearly says on spectrum-based parameters are becoming very popular and cognitive defined systems are found to be near best solution for many communication network applications. Hence this paper provides to develop an algorithm and policy engine makes a details model and study on dynamic spectrum access in cognitive system using continuous time Markov chain process. The detailed and outcome of results clearly shows a 96% of efficiency on the spectrum dynamics which came from our unique proposed model.Â Â